2011
DOI: 10.1080/13600818.2011.594500
|View full text |Cite
|
Sign up to set email alerts
|

Ensuring Daughter Survival in Tamil Nadu, India

Abstract: The south Indian state of Tamil Nadu is a relatively recent addition to the list of Indian states to experience the phenomenon of 'missing girls'. Nonetheless, the government and NGOs in the state have been active for some time in collecting data to track gender differences in survival and in introducing interventions to prevent daughter elimination. Against this background, this article has two aims. First, it provides a temporal and spatial analysis of patterns of daughter deficits in Tamil Nadu over the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The studies were published in a period between 1929 and 2020. Up to the 1980s, there were only thirteen publications [ 15 , 27 , 51 , 54 , 56 , 57 , 61 , 63 – 68 ], and the number increased to 21 in the 1980s [ 8 , 23 , 28 , 34 , 58 , 59 , 69 83 ], 46 in the 1990s [ 3 , 4 , 6 , 12 , 22 , 24 , 33 , 39 , 43 , 44 , 46 , 49 , 52 , 53 , 84 – 115 ], decreased to 30 in the 2000s [ 7 , 11 , 16 , 17 , 21 , 25 , 26 , 36 , 41 , 47 , 50 , 60 , 62 , 116 132 ], and reached 44 in the period between 2010 and 2020 [ 1 , 2 , 5 , 13 , 14 , 18 20 , 29 32 , 35 , 37 , 38 , 40 , 42 , 45 , 48 , 55 , 133 156 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The studies were published in a period between 1929 and 2020. Up to the 1980s, there were only thirteen publications [ 15 , 27 , 51 , 54 , 56 , 57 , 61 , 63 – 68 ], and the number increased to 21 in the 1980s [ 8 , 23 , 28 , 34 , 58 , 59 , 69 83 ], 46 in the 1990s [ 3 , 4 , 6 , 12 , 22 , 24 , 33 , 39 , 43 , 44 , 46 , 49 , 52 , 53 , 84 – 115 ], decreased to 30 in the 2000s [ 7 , 11 , 16 , 17 , 21 , 25 , 26 , 36 , 41 , 47 , 50 , 60 , 62 , 116 132 ], and reached 44 in the period between 2010 and 2020 [ 1 , 2 , 5 , 13 , 14 , 18 20 , 29 32 , 35 , 37 , 38 , 40 , 42 , 45 , 48 , 55 , 133 156 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some authors reported on female-to-male sex ratios for mortality, but most presented results as male-to-female ratios, either as a simple ratio or multiplied by 100, with values of 1 and 100, respectively, indicating equality between boys and girls. Also, in some of them, the excess mortality of girls was estimated [ 2 , 14 , 18 20 , 42 , 93 , 102 , 109 , 132 , 153 , 154 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations